Issues related to differential diagnosis of epilepsy and narcolepsy - E. A. Kantimirova; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
A differential diagnosis of epileptic and non-epileptic paroxysms is particularly difficult to conduct during a neurologist consultation. Narcolepsy is a chronic disease that causes excessive daytime sleepiness. Some narcolepsy symptoms, especially cataplexy, can be mistakenly interpreted as epileptic seizures. The clinical case demonstrates an importance for interdisciplinary approach to differential diagnosis of epileptic seizures. Clinical markers of typical and atypical cataplexy manifestations are presented.